THE NEED FOR A COMMON CORPORATE GOVERNANCE FRAMEWORK FOR CORPORATIONS OF DIFFERENT STATES - L. Ushvitskiy; E. Didenko (Вестник Северо-Кавказского федерального университета, 2022)
The paper examines one of the major global trends in corporate governance related to the establishment of common economic frameworks for corporations of different States and the rule of law. The need to create a common basis for corporate governance for Russian corporations, i.e. on the basis of an analysis of the positions of Russian and foreign economists, has been substantiated. Obstacles to the integration of Russian corporations into the European and international economic space have been identified. As a practical justification for the need for corporate integration, transnational business models have been constructed, reflecting the difficulties of implementing corporate governance in Russia with foreign investment. The conclusions on the need to create a transparent economic space and common structures of legal entities to increase the efficiency of corporate governance and the integration of Russian corporations into the European Economic Area have been substantiated.